CHALLENGES OF STRATEGY IMPLEMENTATION: A CASE STUDY OF KENYA MEDICAL TRAINING COLLEGE - Ndunge, Dr. Miriam M.; Oluoch, Dr.Kelly; Mutua, Dr.Caleb. M. (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of this study was to determine the challenges that affect the implementation of strategic plan at KMTC. Methods: This study adopted a case study research design. The study used both primary and secondary data. The study population was the KMTC headquarters offices and all constituent KMTC campuses which had the chance of implementing the strategic plans (http//www. kmtc.ac.ke on 24th February 2015). The study respondents was the top management at the KMTC headquarters, principals and HOD of various satellite KMTC campuses. Primary Data was collected with the help of a semi structured questionnaire The study was a Census involving all the 28 KMTC campuses which had the chance of implementing both strategic plans to completion. Data was analyzed by use of SPSS (Statistical Package for Social Science). The descriptive statistics such as tabulations, percentages, mean, standard deviation and frequencies was used in the data presentation. Results: The findings of the study are that the strategic plan had been implemented satisfactorily at the institution with various aspects remaining to be streamlined. These areas included communication of the strategic plan organization-wide and monitoring and evaluation of the plan. There were several challenges experienced during the implementation of the plan. The main challenge being inadequate financing of the plan and even where the plan financed, late disbursement was experienced. Unique Contribution to Theory, Practice and Policy: The study recommends that a proper monitoring and evaluation system be put in place and that a proper communication system be in place to update staff on the plan. The researchers further recommend that an office be created to oversee the implementation of the plan.